A fishery manager's guidebook - Cochrane, K. L.; Garcia, Serge (Wiley-Blackwell, 2009)
Identifies the primary tasks in the management of capture fisheries, with particular emphasis on sustainable utilization of biological resources and demonstrates how these tasks should be undertaken in an integrated and coordinated manner to obtain the desired benefits from the biological resources in a sustainable and responsible manner.